Stigmasterol mitigates estrogen-deficiency-induced osteoporosis through inhibition of phosphorylated p65 and MAPK signaling pathways - Zhao, Qiangqiang; Chen, Xingling; Mai, Bin; Che, Feihong; Zhang, Zhen; Kang, Pan; Hou, Chengyu; Lu, Lu; Xu, Liangliang (Frontiers in Pharmacology, 2024)
BackgroundOsteoporosis is a pervasive bone metabolic disorder characterized by the progressive degeneration of bone microstructure. Osteoclasts are playing a pivotal role in bone remodeling and resorption. Consequently, modulating osteoclast activity, particularly curbing their overactivation, has become a crucial strategy in clinical treatments. Stigmasterol (STG), a plant-derived phytosterol, has shown promise in inhibiting osteoclastic activity, although its precise biological mechanisms require further scientific investigation. Therefore, this study aims to explore the potential mechanisms by which STG inhibits osteoclasts and to further assess its impact on osteoporosis by establishing an Ovariectomy (OVX) model.MethodsInitially, osteoclast differentiation was induced in vitro using RANKL (Receptor Activator of Nuclear Factor Kappa-B Ligand) on RAW 264.7 cells, followed by TRAP staining and F-actin banding to observe the effects of various concentrations of STG during osteoclast differentiation. The osteoclast-specific gene and protein expression changes were further analyzed using Real-Time PCR (qPCR) and Western blot, exploring the RANKL-mediated NF-κB and MAPK signaling pathways. An OVX model was established in vivo to examine changes in bone mass through Micro-CT and Hematoxylin and eosin (H&E) staining, and to assess osteoclast formation and characteristic protein expression through TRAP staining and Immunohistochemistry staining.ResultsIn vitro experiments revealed that STG significantly inhibited osteoclast activity, as evidenced by reductions in osteoclast numbers and spreading areas, and a marked suppression of F-actin formation. On the molecular level, this compound effectively downregulated key osteoclast markers such as NFATc1, Acp5, c-Fos, and ΜMP9 in both gene and protein expressions. Western blot analysis showed that STG notably inhibited the phosphorylation of the p65 subunit in the NF-κB pathway, thus affecting the pathway’s activity. Further validation through OVX model indicated significant protective effects of STG against bone loss, as demonstrated by Micro-CT. Histopathological staining confirmed STG’s efficacy in reducing bone surface area and volume loss. Additionally, TRAP staining showed significant reductions in osteoclast number and surface area in the STG group compared to the OVX group, underscoring STG’s potential therapeutic role in bone metabolism regulation.ConclusionThe findings reveal that STG effectively inhibits the phosphorylation of the p65 protein in the NF-κB pathway, and influences the MAPK signaling pathway, thereby reducing osteoclast formation and preserving bone mass. These mechanisms provide a crucial molecular basis for its potential therapeutic application in treating osteoporosis.